2002
DOI: 10.1109/ted.2002.801430
|View full text |Cite
|
Sign up to set email alerts
|

Determination of channel temperature in AlGaN/GaN HEMTs grown on sapphire and silicon substrates using DC characterization method

Abstract: Self-heating effects and temperature rise in AlGaN/GaN HEMTs grown on silicon and sapphire substrates are studied, exploiting transistor dc characterization methods. A negative differential output resistance is observed for high dissipated power levels. An analytical formula for a source-drain current drop as a function of parasitic source resistance and threshold voltage changes is proposed to explain this behavior. The transistor source resistance and threshold voltage is determined experimentally at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 19 publications
8
113
0
Order By: Relevance
“…The equipment needed for these temperature assessments is available in standard electrical testing laboratories. Different methods are used, all based on measuring changes in temperature dependent electrical parameters, including: Saturated drain current [10][11][12][13][14]; gate leakage current and threshold voltage, among other parameters. These techniques offer no spatial resolution as such, but instead are sensitive to the entire periphery of the device channel [14].…”
Section: Techniquesmentioning
confidence: 99%
“…The equipment needed for these temperature assessments is available in standard electrical testing laboratories. Different methods are used, all based on measuring changes in temperature dependent electrical parameters, including: Saturated drain current [10][11][12][13][14]; gate leakage current and threshold voltage, among other parameters. These techniques offer no spatial resolution as such, but instead are sensitive to the entire periphery of the device channel [14].…”
Section: Techniquesmentioning
confidence: 99%
“…These properties include a high sheet carrier concentration, high mobility, and high critical electric field. High power applications require high power densities in the active region of these devices, which leads to highly localized Joule self-heating and potentially high peak temperatures [3,4]. Commercial applications now exist for GaN HEMTs, often operated in pulsed mode, although performance is typically de-rated for the purpose of thermal management and maintaining channel temperatures within a safe operating area, in particular, avoiding thermally activated degradation of the gate Schottky contact [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to apply this technique to GaN devices due to degradation of the Schottky barrier with any sizeable gate current [6]. Using dc characteristics to measure channel temperature has also been proposed in GaN HEMTs [7], [8]. However, we have found that a dc measurement technique becomes problematic at high voltage because it can be cumbersome to remove the change in I D induced by current collapse in GaN HEMTs.…”
Section: Introductionmentioning
confidence: 99%